Effect of feeding wood kraft pulp on the growth performance, feed digestibility, blood components, and rumen fermentation in Japanese Black fattening steers. (27th February 2019) - Maeda, Yuka; Nishimura, Keiko; Kurosu, Kazuhiro; Mizuguchi, Hitoshi; Sato, Shigeru; Terada, Fuminori; Kushibiki, Shiro
Abstract: This study aimed to examine the effects of feeding kraft pulp (KP) on the growth performance, feed digestibility, and rumen fermentation of Japanese Black fattening steers. Ten Japanese Black fattening steers (aged 26 months) were randomly divided into control and KP groups. The control group ( n = 5) was fed concentrate feed without KP, and the KP group ( n = 5) was fed concentrate feed containing 10% KP. Both the groups were provided rice straw as roughage. The experiment was conducted over a period of 12 weeks. There was no significant difference in dry matter intake, daily body weight gain, and nutrient digestibility between both groups. No difference was observed in the ruminal concentrations of volatile fatty acids among the groups. At weeks 8 and 12 after the onset of the experiment, the acetate‐to‐propionate ratio in the ruminal fluid of the KP group was significantly higher than that of the control group. The average daily pH of ruminal fluid and activity of ruminal lipopolysaccharide did not differ between the groups. Our results suggested that the growth performance and feed digestibility in the Japanese Black fattening steers were not influenced by replacing concentrate feed with KP.